2017
DOI: 10.1001/jamadermatol.2017.1976
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Receptor Polymorphisms With the Risk of Nonmelanoma Skin Cancer in Adults

Abstract: IMPORTANCE Protective effects of UV-B radiation against nonmelanoma skin cancer (NMSC) are exerted via signaling mechanisms involving the vitamin D receptor (VDR). Recent studies have examined single-nucleotide polymorphisms (SNPs) in the VDR, resulting in contradictory findings as to whether these polymorphisms increase a person's risk for NMSC.OBJECTIVE To examine whether the polymorphisms in the VDR gene are associated with the development of NMSC and the demographic characteristics of the participants. DES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Five papers reported on the association between any of five polymorphisms of the VDR gene ( Apa1 , Bsm1 , Cdx2 , Fok1 , and Taq1 ) and NMSC risk [ 13 , 29 , 30 , 31 , 32 ]. The studies were conducted in the USA (n = 2) and Europe (n = 3) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five papers reported on the association between any of five polymorphisms of the VDR gene ( Apa1 , Bsm1 , Cdx2 , Fok1 , and Taq1 ) and NMSC risk [ 13 , 29 , 30 , 31 , 32 ]. The studies were conducted in the USA (n = 2) and Europe (n = 3) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, VDR activity can be influenced by single-nucleotide polymorphisms (SNPs) [254]. This plays, for example, a role in the etiology of nonmelanoma skin cancers (NMSC) and melanoma [38,54,104,111,117]. Interestingly, CYP11A1-derived D3 hydroxyderivatives without a hydroxyl group at C1α display a subset of the activities possessed by 1,25(OH) 2 D3 (see above) and lack calcemic activity, acting as biased agonists on the VDR [197,207].…”
Section: Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…In a Polish population, the TT genotype of FokI VDR polymorphism was correlated with greater than tenfold higher risk of BCC development [111]. Burns et al found that the BsmI b or TaqI t genotypes of VDR were more frequent in NMSC patients, suggesting that individuals with these genotypes are more likely to develop skin cancer [38]. A very recent nested case control study and meta-analysis showed that patients with rs2228570, rs927650, and rs1544410 recessive genotypes were characterized by a lower risk of SCC development, while rs7975232 and rs739837 recessive genotypes were related to decreased BCC risk [107].…”
Section: Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…It is interesting that vitamin D is both produced in the skin and exerts its effects on the skin via VDR. VDR transcription rate depends on the availability of VDR agonists and antagonists and can also be influenced by singlenucleotide polymorphisms, which play a role in the etiology of NMSC [28][29][30][31][32][33]. In the skin, VDR expression can fluctuate based on the pathology of skin conditions.…”
Section: Vitamin D Mechanism Of Actionmentioning
confidence: 99%